Short and Efficient Chemoenzymatic Syntheses of non‐Natural (−)‐Muscarine and (+)‐allo‐Muscarine from Cyano‐Sugar Precursors Catalyzed by Immobilized Burkholderia cepacia Lipase. Issue 1 (21st December 2016) - Carnero, Alejandro; Sanghvi, Yogesh S.; Gotor, Vicente; Fernández, Susana; Ferrero, Miguel
Abstract: Enantiopure (2 R )‐configured non‐natural (−)‐muscarine and (+)‐ allo ‐muscarine were efficiently synthesized by a chemoenzymatic approach from an easily accessible cyano‐sugar available on a large‐scale. The key enzymatic hydrolysis step was accomplished by immobilized Burkholderia cepacia lipase (also known as Pseudomonas cepacia lipase, PSL‐IM). The PSL‐IM‐mediated regioselective hydrolysis of the 5‐ O ‐toluoyl ester group in α‐ and β‐cyano‐sugars, furnished 3‐ O ‐toluoyl‐α‐cyano‐sugar and 3‐ O ‐toluoyl‐β‐cyano‐sugar, respectively, with total selectivity and in excellent yields. To demonstrate the industrial utility of this method, 3‐ O ‐toluoyl‐β‐cyano‐sugar was synthesized on a 10 g scale using PSL‐IM and the catalyst was reused. A key feature of the synthesis route described herein is the simultaneous hydrogenolysis of a tosyl group, reduction of a nitrile and deprotection of a toluoyl group using LiAlH4 in a one‐pot procedure. This study offers a green protocol for synthesis of two muscarine derivatives in high yields employing a concise four‐step strategy. Abstract :